2020
DOI: 10.3390/agriculture10070282
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and Intermittent Drying of Rough Rice: Effects on Process Effective Time and Effective Mass Diffusivity

Abstract: The choice of the drying process plays a key role in reducing the costs of electricity consumption in the food industry. Thus, this study aimed to evaluate continuous and intermittent drying of rough rice, using empirical and diffusion models to describe the drying kinetics, considering only effective time of operation to compare and evaluate these processes. Experiments were carried out during the month of April 2018, in Campina Grande, Paraiba Brazil, and were conducted with continuous and intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In general, it was found that all intermittency levels studied here, with intermittency ratio α = 2/3, had similar final process times, proving to be efficient in relation to energy consumption. Pereira et al (2020), in the drying of rough rice, also showed that intermittent drying produced a similar effect on drying kinetics, highlighting the feasibility of using intermittent drying of rough rice with intermittency ratio α = 2/3 for temperatures of 50 and 70 °C. The results also suggest that the 30-min tempering period was more adequate than the 20-min tempering period.…”
Section: Results Obtained By the Mathematical Modelsmentioning
confidence: 66%
See 1 more Smart Citation
“…In general, it was found that all intermittency levels studied here, with intermittency ratio α = 2/3, had similar final process times, proving to be efficient in relation to energy consumption. Pereira et al (2020), in the drying of rough rice, also showed that intermittent drying produced a similar effect on drying kinetics, highlighting the feasibility of using intermittent drying of rough rice with intermittency ratio α = 2/3 for temperatures of 50 and 70 °C. The results also suggest that the 30-min tempering period was more adequate than the 20-min tempering period.…”
Section: Results Obtained By the Mathematical Modelsmentioning
confidence: 66%
“…According to Putranto et al (2011), intermittent drying reduces the effective drying time using hot air, thus reducing energy consumption per unit of removed mass, being an effective method to improve the drying rate and product quality. Pereira et al (2020), in their study on the continuous and intermittent drying of rough rice, with intermittency ratio of α= 2/3, concluded that, in a comparison between continuous and intermittent drying kinetics, drying time was reduced with the application of intermittency, promoting greater energy saving. It was verified that the boundary condition of the first type was the one which best describes the drying process of rough rice and that the effective mass diffusivity increased with intermittent drying.…”
Section: Intermittent Drying and Energy Efficiencymentioning
confidence: 99%
“…In addition to empirical models, the process of water absorption by rice grains was also described by a diffusion model, fitted to the experimental data. Based on the literature, for grains, the usual boundary condition for the diffusion equation is of the first kind (Silva et al , 2012; Morais et al , 2013; Lima et al , 2018; Pereira et al , 2020). Thus, to solve the diffusion equation by separation of variables, it was assumed that the boundary condition could be considered as first kind.…”
Section: Methodsmentioning
confidence: 99%
“…In this process, rice grains, still with husk, are immersed in water at a temperature above 58 °C and then subjected to processes of partial or total gelatinization of starch. Thus, some water-soluble substances, such as vitamins and minerals, are transported to the center of the grain, increasing the nutritional value of this rice compared to polished rice (Buggenhout et al , 2013; Pereira et al , 2020). Finally, the parboiling process ends with the drying and refinement stages, where the rice grain becomes more resistant to breakage, in addition to reducing susceptibility to insect attack and increasing the industrial yield (Demont et al , 2012; Martins et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Chen, et al [12] carried out an orthogonal experiment involving hot air drying with variable temperature and humidity and established a comprehensive target model; the drying process was optimized by a genetic algorithm. Alves Pereira, et al [13] used empirical and diffusion models to describe rice drying kinetics, and considered only effective time of operation to compare and evaluate continuous and intermittent drying of rough rice. This study proved that a one-dimensional diffusion model could describe the drying process of rice properly, and found that the effective mass diffusivity was higher in intermittent drying as compared to continuous drying at the same temperature.…”
Section: Introductionmentioning
confidence: 99%